Prevalent Diagnosis of Orofacial Fissures in a Reference Service with Resident Cases in the State of Mato Grosso do Sul - Gardenal, Mirela; Bastos, Paulo Roberto Haidamus de Oliveira; Pontes, Elenir Rose Jardim Cury; Bogo, Danielle (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The orofacial fissures are among the most frequent congenital malformations and show a clinical diversity, causing a series of severe complications permanently observed in the individual through his/her lifetime.Objective: To estimate the prevalent types of congenital orofacial fissures diagnosed in a reference service with resident cases in the State of Mato Grosso do Sul from January 2003 to December 2007.Method: An observation study of transverse incision was performed, whose data was obtained from the records at Rehabilitation Hospital of Craniofacial Anomalies (HRAC/USP/SP). To calculate the prevalence, live-born data (SINASC) was used.Results: In brief, there were 271 diagnosed cases in the reference service, with the unilateral incisive trans-foramen fissures prevailing for the left side, which mostly attacked the male gender and white ethnicity. The mother's average age was 25 and her school education was from 9 to 11 years, with a history of pregnancy complications and without prior fissures. At SINASC, 98 cases of fissure were noticed for the same period, corresponding to a prevalence of 0.49 per 1,000 births.Conclusion: In the present study, it was possible to estimate the prevalence of fissure by the data from both the Hospital and SINASC, but future studies regarding the orofacial fissures epidemiology in the State of Mato Grosso do Sul and the Midwestern Region, using uniform terminology for classification purposes, are necessary to compare and follow up with the seasonal evolution of prevalence.
Keywords: Epidemiology; prevalence; palatine fissure; cleft lip